Enhancement of Teaching Methods of Main Mathematical Disciplines in Higher School - A. N. Vybornov; Zh. G. Vegera (Цифровая трансформация, 2024)
Innovations are proposed in the courses of mathematical analysis, linear algebra and discrete mathematics taught in the first year of study. Innovations are aimed at improving methods of teaching basic mathematical disciplines in higher education.